Supervision of Islamic Culture at MTs Darul Ihya Ciomas - Yudi Efendi; Wido Supraha (At-Takwin: Journal of Islamic Education Studies, 2025)
This study aims to explore the implementation of Islamic culture within the school environment as a strategic effort to develop students’ religious character, focusing on a case study at MTs Darul Ihya, Ciomas, Bogor. Drawing upon Syed Muhammad Naquib al-Attas’s concept that education is the instillation of meaningful knowledge (ʿilm) leading to adab (proper behavior), the research emphasizes the balanced integration of knowledge, skills, and attitudes in Islamic education. Employing a qualitative approach with in-depth interviews and data triangulation, the study investigates how Islamic Education (PAI) teachers promote Islamic values through structured habituation programs such as congregational prayers, Qur’an recitation, morning dhikr, and daily adab practices. Supervision results indicate a fairly strong implementation of Islamic cultural values, with an average score of 78%, although certain areas—such as Qur’an reading habits and student brotherhood—require further reinforcement. These findings highlight the importance of continuous supervision that is not only evaluative but also reflective and solution-oriented. With collaborative involvement from all school stakeholders, Islamic cultural values can be effectively integrated into daily school life, fostering a generation that is intellectually capable, well-mannered, and grounded in both Islamic and national values.